Effectiveness Of Selected Midwifery Activities Regarding Active Management Of Third Stage Of Labour (International Journal of Food and Nutritional Sciences, 2023)
The third stage of labour’s managed funds was essential in preventing haemorrhage connected to childbirth. However, there is a significant amount of maternal mortality and morbidity related to haemorrhage because reproductive healthcare workers lack knowledge and skills about just the active management of the second and third trimester. Our The purpose of this research was to assess midwives' capabilities in India to carefully manage the fourth phase of labour by examining their understanding, tactics, routines, and associated factors. Midwives were the subject of a hospital- based cross-sectional research from December 2020 to December 2022. The midwives are questioned to collect data. During the study period, the health authority documented births from over 9,000 women annually. The final section of labour may be managed by midwives thanks to their training and experience. After accounting for any confounding factors, the findings showed that having a midwife constituted one of the key predictors of effective active administration of the second and third trimester. The awareness and education of paediatricians concerning the actively managed funds of the second and third trimester may be improved with the specific strategies, such as ongoing training sessions. This research also made it very evident that midwives' knowledge and skill levels regarding active management of the third stage of labour need rapid correction. To improve skill, hospitals should organise trainings for more midwives.